Neurological Response to cART vs. cART plus Integrase Inhibitor and CCR5 Antagonist Initiated during Acute HIV. - Victor G Valcour; Serena S Spudich; Napapon Sailasuta; Nittaya Phanuphak; Sukalaya Lerdlum; James L K Fletcher; Eugene D M B Kroon; Linda L Jagodzinski; Isabel E Allen; Collin L Adams; Peeriya Prueksakaew; Bonnie M Slike; et al. (PLoS ONE, 2015)
To compare central nervous system (CNS) outcomes in participants treated during acute HIV infection with standard combination antiretroviral therapy (cART) vs. cART plus integrase inhibitor and CCR5 antagonist (cART+).24-week randomized open-label prospective evaluation.Participants were evaluated then randomized to initiate cART (efavirenz, tenofovir, and either emtricitabine or lamivudine) vs. cART+ (cART plus raltegravir and maraviroc) during acute HIV and re-evaluated at 4, 12 and 24 weeks. We examined plasma and CSF cytokines, HIV RNA levels, neurological and neuropsychological findings, and brain MRS across groups and compared to healthy controls.At baseline, 62 participants were in Fiebig stages I-V. Randomized groups were similar for mean age (27 vs. 25, p = 0.137), gender (each 94% male), plasma log10 HIV RNA (5.4 vs. 5.6, p = 0.382), CSF log10 HIV RNA (2.35 vs. 3.31, p = 0.561), and estimated duration of HIV (18 vs. 17 days, p = 0.546). Randomized arms did not differ at 24 weeks by any CNS outcome. Combining arms, all measures concurrent with antiretroviral treatment improved, for example, neuropsychological testing (mean NPZ-4 of -0.408 vs. 0.245, p<0.001) and inflammatory markers by MRS (e.g. mean frontal white matter (FWM) choline of 2.92 vs. 2.84, p = 0.045) at baseline and week 24, respectively. Plasma neopterin (p<0.001) and interferon gamma-induced protein 10 (IP-10) (p = 0.007) remained elevated in participants compared to controls but no statistically significant differences were seen in CSF cytokines compared to controls, despite individual variability among the HIV-infected group.A 24-week course of cART+ improved CNS related outcomes, but was not associated with measurable differences compared to standard cART.